Biochar and Azolla Effects on Soil Chemical Properties, Lead Content and Growth of Paddy - Mayly, Syarifa; Hidayat, Benny (Agro Bali : Agricultural Journal, 2024)
The objective of the study was to determine the influences of biochar amendments and Azolla sp application on soil chemical value, lead (Pb) content,  and growth of paddy. The research was conducted in Growth Centre LLDIKTI I, Medan, Sumatera Utara, Indonesia, from April to July 2014. The research design used a factorial randomized block design with three replications. The first factor was Azolla sp application: without Azolla (A0); Azolla pinnata (A1); Azolla mikropilla (A2)] and the second factor was biochar amendment without biochar (B0); RSB-Rice straw biochar (B1),  RHB-Rice husk biochar (B2), CPB-coconut peat biochar (B3), OPB-Oil Palm Empty Bunch biochar (B4)]. The result showed that the biochar amendment treatments had significant differences (P<0.05) in all soil chemical values and growth parameters of paddy. The Azolla application showed significant differences (P<0.05) in plant height, number of tillers, shoot dry weight, root dry weight, and Pb content in the root. The interaction among the Azolla sp and the biochar amendments showed significant differences (P<0.05) in a number of the tillers. It was concluded that the application of rice husk biochar and Azolla microphylla was able to increase soil chemical properties, increase the growth of paddy, and also increase the Pb content in soil, leaves, and roots.